Functional liposome loaded curcumin for the treatment of Streptococcus mutans biofilm - Hu, Zhimin; Tang, Ying; Jiang, Bulin; Xu, Yue; Liu, Siying; Huang, Cui (Frontiers in Chemistry, 2023)
Introduction: Plaque biofilms, mainly formed by Streptococcus mutans (S. mutans), play an important role in the occurrence and development of dental caries. Antibiotic treatment is the traditional way to control plaque. However, problems such as poor drug penetration and antibiotic resistance have encouraged the search for alternative strategies. In this paper, we hope to avoid antibiotic resistance through the antibacterial effect of curcumin, a natural plant extract with photodynamic effects, on S. mutans. However, the clinical application of curcumin is limited due to its low water solubility, poor stability, high metabolic rate, fast clearance rate, and limited bioavailability. In recent years, liposomes have become a widely used drug carrier due to their numerous advantages, such as high drug loading efficiency, high stability in the biological environment, controlled release, biocompatibility, non-toxic, and biodegradability. So, we constructed a curcumin-loaded liposome (Cur@LP) to avoid the defect of curcumin. Methods: Cur@LP functioned with NHS can adhere to the surface of the S. mutans biofilm by condensation reaction. Liposome (LP) and Cur@LP was characterized by transmission electron microscopy (TEM) and dynamic light scattering (DLS). The cytotoxicity of Cur@LP was evaluated by CCK-8 assay and LDH assay. The adhesion of Cur@LP to S. mutans biofilm was observed by confocal laser scanning microscope (CLSM). The antibiofilm efficiency of Cur@LP were evaluated by crystal violet staining, CLSM, and scanning electron microscope (SEM). Results: The mean diameter of LP and Cur@LP were 206.67 ± 8.38 nm and 312 ± 18.78 nm respectively. The ζ-potential of LP and Cur@LP were ∼−19.3 mV and ∼−20.8 mV respectively. The encapsulation efficiency of Cur@LP was (42.61 ± 2.19) %, and curcumin was rapidly released up to ±21% at 2 h. Cur@LP has negligible cytotoxicity, and can effectively adhered to the S. mutans biofilm and inhibited its growth. Discussion: Curcumin has been widely studied in many fields such as cancer, which can be attributed to its antioxidant and anti-inflammatory effects. At present, there are few studies on the delivery of curcumin to S. mutans biofilm. In this study, we verified the adhesion and antibiofilm of Cur@LP to S. mutans biofilm. This biofilm removal strategy has the potential to be translated into the clinic.